CATCH 2023 Meeting Summary: Collaborate & Address Treatment Challenges in Haemophilia - Benson Gary; Curry Nicola; Fletcher Simon; Gregory Will; Harrison Cathy; Laffan Mike; Lowe Gillian; Khair Kate; Kirk Susan; McLaughlin Paul; Percy Charles; Player Denise; et al. (The Journal of Haemophilia Practice)
Access to treatment and healthcare services for people with haemophilia in the United Kingdom (UK) and Republic of Ireland ranks highly by international standards for contemporary haemophilia management. Collaborate & Address Treatment Challenges in Haemophilia (CATCH) is an annual Sobi™ medical education meeting which brings together multidisciplinary haemophilia treaters throughout the UK and Ireland to discuss all aspects of haemophilia management, including associated challenges and unmet need. This report summarises key issues explored and discussed during CATCH 2023, including ‘raising the bar’ in haemophilia care; haemophilia care for women and girls; changing haemophilia treatment paradigms to consider disease impact as well disease severity; bone health and haemophilia; and shared decision-making.